Organic Amendments Application Increases Yield and Nutrient Uptake of Mustard (Brassica Juncea) Grown in Chromium-Contaminated Soils. Issue 1 (2nd January 2020) - Kumar, Vipin; Sharma, Pramod Kumar; Jatav, Hanuman Singh; Singh, Satish Kumar; Rai, Ashish; Kant, Surya; Kumar, Achin
ABSTRACT: A pot experiment (Net House) study was conducted in the Department of Soil Science and Agriculture Chemistry, Institute of Agricultural Science, B.H.U. Varanasi to find out the effect of organic amendments in mustard grown in chromium (Cr)-contaminated soil during 2015–16 and 2016–17. There were five levels of Cr (Control, 20, 40, 60 and 80 mg/Kg soil) with and without three organic amendments ( viz . Vermicompost (VC), FYM, and Sewage Sludge (Sl)) @ 5 t/ha, 10 t/ha and 20 t/ha, respectively. The maximum number of siliqua/plant (333 and 354), length of siliqua (5.43 and 5.53), number of seeds per siliqua (12.11 and 12.39), dry matter accumulation (50.76 and 54.65g/pot), biological yield (266.51 and 273.34g/pot), seed yield (62.63 and 66.96g/pot), stover yield (203.88 and 206.38g/pot), and harvest index (23.50 and 24.5%) were recorded when Cr-contaminated soil is treated with organic amendments mainly with vermin compost during 2015–16 and 2016–17. It is reported that significant nutrient uptake (N, P, S, K, Fe, Cu, Zn, and Mn) also increased with the application of organic amendments. It is reported that yield attributing characters are improved by the application of VC followed by farm yard manure then sewage Sl.